Case Report: Diagnosis and Treatment of Psychosomatic Gastritis at a Primary Health Clinic in West Surabaya, Indonesia - Roosihermiatie, Betty; Isfandari, Siti; Fauzia, Yurika (Folia Medica Indonesiana, 2018)
Indonesia is highly populated of a total 238,452,952 people with 274,396 gastritis cases. However, psychosomatic gastritis was just reported by very few patients. Because of the common gastritis cases in Indonesia and with the act of Healthcare and Social Security Agency or BPJS, so primary health cares should diagnose and manage the cases. This study aimed to determine the diagnosis and management of psychosomatic gastritis at a primary health clinic in West of Surabaya. It was a case study. It was a case on a woman aged 45 years old. She was high school graduate, married and had a child. She experienced reflux gastritis and psychiatric condition of depression and anxienty disorders. She was treated by psychiatrist at the first time and self-medicated for the gastritis. After stopping visiting the psychiatrist, she had problems of gastritis in four months. Then, she was referred to internist and examined Ultra Sonography of abdominal organs with normal result. There was a conventional method to determine psychosomatic gastritis that consicting of life styles, psychologic factor, social factor, and behavior assessment. This patient was a local migrant who struggled to gain a better life in the city, had a trigger for his father's death, had a relatively low socioeconomic state and lived in a monthly boarding house, and was a part-time worker. First-line care should establish a psychosomatic diagnosis of gastritis and treat psychological disorders together with their somatic abnormalities. Thus, the first level of health services must provide holistic services consisting of physical, psychological and social aspects.